2011
DOI: 10.1002/casp.1102
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Attachment in Immigrant Sociocultural Adaptation and Psychological Distress

Abstract: The study extends recent research on the link between attachment security and the sociocultural and psychological adaptation of immigrants. It was hypothesised that attachment style would moderate the effects of sociocultural adaptation difficulties on psychological distress and the relationship between attachment style and immigrant background variables was explored. The study was correlational and questionnaire-based, including a sample of 172 Brazilian immigrants living in the UK. According to the findings,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Acevedo‐Garcia et al, ). This suggests that some factors may protect immigrant adolescents from the negative effects of challenging conditions and socio‐economic disadvantage (Georgiades et al, ; Sochos & Diniz, ).…”
Section: Introductionmentioning
confidence: 99%
“…Acevedo‐Garcia et al, ). This suggests that some factors may protect immigrant adolescents from the negative effects of challenging conditions and socio‐economic disadvantage (Georgiades et al, ; Sochos & Diniz, ).…”
Section: Introductionmentioning
confidence: 99%
“…Polek et al (2010) agree, stating that secure attachment is positively related to psychological and sociocultural adjustment. Sochos and Diniz (2012) also found that attachment is connected to cultural adjustment, claiming that attachment-related concepts such as the disruption of interpersonal bonds and the increase of environmental stress are also part of the cultural adjustment process and that both secure and dismissive attachment styles are connected to higher levels of sociocultural adjustment in expatriates.…”
Section: Theoretical Frameworkmentioning
confidence: 98%
“…Ainsworth, Blehar, Waters, and Wall (1978) found that children with a secure attachment to their caregivers explored a new environment (or "strange situation") more extensively than those with insecure attachments. This idea of a secure base has been extended to adult attachment theory and research, as well as to the field of cultural adjustment (Polek, Wöhrle, & van Oudenhoven, 2010;Sochos & Diniz, 2012;Wang & Mallinckrodt, 2006). Wang and Mallinckrodt (2006) state that being placed in a new cultural environment is similar to the idea of young children learning to explore new physical surroundings in Ainsworth et al's (1978) Strange Situation.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations